INFLUENCE OF AXIAL COMPRESSOR STAGE SPATIAL OPTIMIZATION ON THRUST-ECONOMICAL CHARACTERISTICS OF CARGO AIRCRAFT GAS TURBINE ENGINE - Volyanskaya, L.G.; Grekov, P.I.; Yurсhenko, O.V. (Proceedings of National Aviation University (archive), 2005)
The article considers the research results of D-27 gas turbine engine thrust-economical characteristics change due to of axial compressor flow path optimization. The applied procedure of optimization takes into account a difference in the shapes of axial compressor stage blades at rest and design mode, redistribution of kinetic energy losses along the blade height. The estimation of parameters of a gas flow in the stage flow path is made by the solution of Navier-Stokes equation complete set.